Trend of sustainability disclosure practices in Bangladesh: A case of two selected banks - Farid, Ahammad Sobhani; Azlan, Amran; Yuserrie, Zainuddin (Universiti Malaysia Perlis (UniMAP), 2011)
The Second International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.